2020
DOI: 10.1155/2020/1582653
|View full text |Cite
|
Sign up to set email alerts
|

Still No Substantial Evidence to Use Prophylactic Antibiotic at Operative Vaginal Delivery: Systematic Review and Meta-Analysis

Abstract: Background. Postpartum maternal infection is still a common problem worldwide, mainly due to obstetric risk factors. The use of prophylactic antibiotic at operative vaginal delivery (OVD), taking it as a standalone risk factor, has been controversial. The purpose of this review was to rigorously evaluate the association of OVD with postpartum infection and shed light on such highly controversial issue. Methods. A computer-based literature search was done mainly in the databases of PUBMED, HINARI health researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…In the latest recommendation from the WHO, it is stated that prophylactic antibiotics is needed for women undergoing OVD. On the other hand, a meta-analysis and systematic review published in 2020 concluded that the risks of postpartum infection at OVD is extremely low unless accompanied by episiotomy or third/fourth degree perineal tear [17]. A systematic review estimated that the reported incidence of childbirth-related perineal trauma wound infection ranged from 0.1-23.6% [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the latest recommendation from the WHO, it is stated that prophylactic antibiotics is needed for women undergoing OVD. On the other hand, a meta-analysis and systematic review published in 2020 concluded that the risks of postpartum infection at OVD is extremely low unless accompanied by episiotomy or third/fourth degree perineal tear [17]. A systematic review estimated that the reported incidence of childbirth-related perineal trauma wound infection ranged from 0.1-23.6% [18].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Rasa nyeri pada ibu nifas akibat Kejadian trauma perineum atau robekan perineum memberikan pengaruh besar terhadap keadaan ibu setelah melahirkan, bahwa kelahiran pervaginam 76,8% mengalami teruma perineum derajat dua dimana kejadian infeksi terjadi 1,9% dimana pada kejadian ini ibu nifas ketergantungan pada dokter tenaga kesehatan sehingga mempengaruhi tingkat kejadian infeksi. 10 infeksi nifas terjadi karena peningkatan pada IL-6 dan Hs-CRP yang memberikan pengaru besar pada massa tubuh > 25, bakteri gram negarif dan gram negarif yang perlu di antisipasi penceganya pada penaganan infeksi nifas. 1 Penelitian ini dibagi kedalam 2 kelompok dimana masing kelompok nilai uji Independen T yang membandingkan antara intervensi yang diberikan ekstrak sidaguri (sida rhombifolia) dan juga tidak mengkomsumsi obat antibiotic nilai mean 3,000 standar deviasi 0,000 dengan control yang tidak diberikan ekstrak sidaguri (sida rhombifolia) dan mengkomsumsi obat antibiotik menunjukan hasil bahwa nilai mean 2,384 standar deviasi 0,650 berdarkan hal tersebut memperlihatkan hasil sampel intervensi yang diberikan ekstrak sidaguri (sida rhombifolia) dan juga tidak mengkomsumsi obat antibiotic lebih memberikan efek yang besar dan tidak beragam di bandingkan dengan control yang tidak diberikan ekstrak sidaguri (sida rhombifolia) dan mengkomsumsi obat antibiotik hal ini juga dapat memperlihatkan bahwa pemberian antibiotik pada ibu nifas yang mengalami robekan perineum lebih baik diberikan pengobatan dengan ekstrak sidaguri (sida rhombifolia) dengan nilai P-Value 0,00.…”
Section: Bahasanunclassified
“…Berhan (2020) mengungkapkan bahwa Pemberian antibiotic profilaksis tidak menunjukan perbedaan penyembuhan luka yang signifikan antara kelompok yang diberikan antibiotok dengan kelompok placebo terhadap penyembuhan luka perineum dan kejadian infeksi pada ibu nifas, penyembuhan luka terlihat berbeda pada kelompok luka perineum dengan episiotomy dan robekan perineum. 10 (Kasmiati, 2023 hlm. 48) Ibu yang telah mengalami infeksi nifas dengan pemberian antibiotic profilaksis mampu menurunkan kejadian luka infeksi perineum dan pemberian antibotik tampa indikasi klnik tidak dibutuhkan.…”
Section: Bahasanunclassified
“…9 Regarding normal vaginal delivery, WHO guidelines 2015 recommend routine antibiotic prophylaxis for women with a third-or fourth-degree perineal tear. 10,11 In 2021, the WHO issued new guidelines recommending single-dose prophylactic antibiotics for women undergoing operative vaginal delivery. 12 Non-obstetrics indication for antibiotics used during pregnancy including respiratory, ear, nose, and throat infections.…”
mentioning
confidence: 99%